2007
DOI: 10.1111/j.1728-4465.2007.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Incidence of Abortion in Pakistan

Abstract: This study applies an indirect estimation method to develop comprehensive national and provincial estimates of the prevalence of abortion and abortion-related morbidity in Pakistan. Data from a health facilities survey and a health professionals survey from 2002 are analyzed to develop estimates of postabortion hospitalizations and of the abortion rate, abortion ratio, and unwanted pregnancy rate. We estimate that 890,000 induced abortions are performed annually in Pakistan, and estimate an annual abortion rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 9 publications
1
54
0
Order By: Relevance
“…Despite this legal prohibition, an estimated 14% of pregnancies are terminated by induced abortion, and the annual abortion rate is 29 per 1000 women of reproductive age [24]; clandestine abortions are performed by partly trained or untrained health workers, increasing the risk of manifold complications. In addition, abortion is linked to several interrelated factors such as non-use of contraceptives, unprotected sex, non-consensual conjugal relations, and unwanted pregnancies [24]. Many studies have found that abortion is more common in abused women [3,4,7,21], although it was not significantly associated with IPV in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this legal prohibition, an estimated 14% of pregnancies are terminated by induced abortion, and the annual abortion rate is 29 per 1000 women of reproductive age [24]; clandestine abortions are performed by partly trained or untrained health workers, increasing the risk of manifold complications. In addition, abortion is linked to several interrelated factors such as non-use of contraceptives, unprotected sex, non-consensual conjugal relations, and unwanted pregnancies [24]. Many studies have found that abortion is more common in abused women [3,4,7,21], although it was not significantly associated with IPV in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…16 This methodology has since been used successfully in other developing countries in Asia, Africa, and Latin America and the Caribbean. 9,[17][18][19][20][21] Using 1990 data for Mexico, Singh and Wulf estimated that 533,000 induced abortions occurred annually, and that the abortion rate was 25 per 1,000 women aged 15-44. * 16 No similar national estimate of abortion incidence has been made for Mexico since their study.…”
Section: Data Sourcesmentioning
confidence: 99%
“…One of the critical requirements for capturing the demographic dividend is to improve the basic levels of education and skills of the working-age population. The strong relationship between education and population well-being has been recognized in countries at all stages of development, and is particularly critical in countries, like Pakistan, that are in the middle stages of the demographic transition (Bongaarts 2011;Sathar 2007). Progress in Pakistan has been gradual.…”
Section: Can Pakistan Have a Rapid Fertility Transition?mentioning
confidence: 99%
“…About one in four births in Pakistan is unwanted, and a similar proportion is mistimed (National Institute of Population Studies 2008). Furthermore, an estimated one million abortions are performed each year, many of them under unsafe conditions (Sathar et al 2007). These unplanned pregnancies contribute to population growth and are a major factor in maternal mortality.…”
Section: Declining Mortalitymentioning
confidence: 99%
See 1 more Smart Citation